Implementasi Model Problem Based Learning (PBL) dengan Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIII D SMP Negeri 15 Palu - Putri Vasra Handayani; Sukayasa; Lantang, Nortje D.J (Papanda, 2025)
This study aims to improve student learning outcomes through the implementation of the Problem-Based Learning (PBL) model combined with the Teaching at the Right Level (TaRL) approach. The research method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of this study were 26 students from class VIII-D at SMP Negeri 15 Palu during the second semester of the 2024/2025 academic year. Data were collected through learning outcome tests and observations, then analyzed using descriptive quantitative techniques. The results showed an improvement in student learning outcomes. This improvement occurred because the PBL model encouraged students to actively participate in the learning process, while the TaRL approach grouped students according to their cognitive abilities, allowing them to solve problems based on their respective skill levels.